Introduction to HIV and Addiction Medicine for Residents: Integrated Case-Based Learning - Rachel Simmons; Jennifer Siegel (Association of American Medical Colleges, 2016)
Abstract Introduction Both HIV and addiction medicine are common clinical issues that medical residents encounter in their training. However, there are projected shortages of providers in both arenas, and studies indicate that trainees have limited exposure to and lack comfort managing these conditions. Within the existing epidemic of opiate use and addiction in Indiana, the HIV outbreak highlights the importance of training on both issues. Therefore, we have developed an innovative, integrated, case-based group learning exercise focusing on treatment of HIV and substance use. Methods The curriculum is designed as a 2-hour module for interns after a degree of clinical exposure to these conditions. Residents in teams work through cases, finding relevant resources and guidelines in real time using computers or wireless devices, then report their findings to the larger group for discussion. The materials associated with this curriculum include a detailed instructor's manual with three discussion cases. We also include a slide set to facilitate interactive discussion of the material, as well as a sample evaluation form and a table with helpful references and resource websites. Results This curriculum has been included as a regular part of our academic half-day for the last 3 years. Most residents indicated relatively low levels of precurricular knowledge about both HIV and addiction. After this module, residents self-reported increased comfort with managing HIV and opiate withdrawal, as well as with identifying resources to help patients with both conditions. Residents reported enjoyment of the integration of these topics and the interactive nature of the material. Discussion An integrated case-based group learning exercise highlighting practical cases involving HIV and substance use has been well received, engaging, and able to increase resident comfort with addressing these often comorbid conditions.